KOMPOSISI DALAM SENI FOTOGRAFI - Herlina, Yekti (Institute of Research and Community Outreach - Petra Christian University, 2007)
The art of photography is not only a simple record of the real world, but becomes a complex creation of art and an image medium that also gives meaning and message. The quality of a good photo is not only becouse of its clear picture but also because of its proper lighting and also its good composition. Composition contains the elements of an image in a format. An image can be produced more effectively and meaningfully with an understanding of good composition. Composition is an instrument for a photographer to take the viewer beyond the experience of “peeking through someone else’s window. Abstract in Bahasa Indonesia: Seni fotografi bukan sekedar merupakan rekaman apa adanya dari dunia nyata, tapi menjadi karya seni yang kompleks dan media gambar yang juga memberi makna dan pesan. Foto yg baik tidak cukup hanya tajam gambarnya, tetapi juga tepat pencahayaannya dalam bidang gambar dengan komposisi yang baik pula. Komposisi adalah rangkaian elemen gambar dalam suatu ruang/format. Dengan komposisi yang baik, foto akan lebih efektif menampilkan pesan pembuatnya dan menimbulkan dampak yang lebih kuat. Komposisi foto merupakan salah satu cara bagaimana fotografer mengekspresikan dirinya. Kata kunci: seni, fotografi, komposisi.